2021
DOI: 10.1016/j.schres.2019.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome in serious mental illnesses: A systematic review and critical evaluation

Abstract: Schizophrenia and bipolar disorder (BD) are associated with debilitating psychiatric and cognitive dysfunction, worse health outcomes, and shorter life expectancies. The pathophysiological understanding of and therapeutic resources for these neuropsychiatric disorders are still limited. Humans harbor over 1000 unique bacterial species in our gut, which have been linked to both physical and mental/cognitive health. The gut microbiome is a novel and promising avenue to understand the attributes of psychiatric di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 115 publications
(168 reference statements)
0
42
0
Order By: Relevance
“…However, animal studies lacked reporting and should therefore be interpretate carefully. Overall, alterations and lack of reporting can be potential cofounding factors [further extensive review elsewhere (42)]. Methodological difference should be standardised in the future to improve translatability between animal and human studies and would allow for improved interpretation of data.…”
Section: Fecal Sample Methodsology Cofoundersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, animal studies lacked reporting and should therefore be interpretate carefully. Overall, alterations and lack of reporting can be potential cofounding factors [further extensive review elsewhere (42)]. Methodological difference should be standardised in the future to improve translatability between animal and human studies and would allow for improved interpretation of data.…”
Section: Fecal Sample Methodsology Cofoundersmentioning
confidence: 99%
“…Furthermore, we identified potential factors particular to psychosis, which may contribute to the altered gut microbiome. The methodology of the studies covered was not described in details as these were extensively reviewed elsewhere (42). Compared to previous reviews (43) we provide detailed discussion of factors such as antipsychotic use, lifestyle and environmental factors as well as the potential pathological role of the microbiome in psychosis relevant to microbial changes.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are live microorganisms which confer health benefits in hosts when administered in appropriate amounts ( FAO/WHO, 2001 ). Several studies that investigated the effect of probiotics on human health have reported that probiotics can be used as a bacteriotherapy for a variety of diseases including psychiatric disorders such as major mental illness ( Butler et al., 2019 ; Nguyen et al., 2019 ). Similarly, several probiotics, such as Lactobacillus , Bifidobacterium , and yeasts, have been investigated as diet additives or alternatives to antibiotics for improving production and health in broilers ( Pelicia et al., 2004 ; Alavi et al., 2012 ; Mohammed et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ruminococcaceae abundance has been demonstrated to be significantly lower in non-alcoholic fatty liver disease (NAFLD) patients than non-NAFLD patients [36], and relatively decreased in bipolar disorder [37]. The relative abundance of Lachnoclostridium, Tyzzerella subgroup 4, Flavonifractor, and…”
Section: Discussionmentioning
confidence: 99%